Effect of 5-R-Thio-Tetrazolo[1,5-C]Quinazoline Derivatives on the Physical Performance in Different Types of Physical Exercise - Kryvoviaz, Olena (Asian Journal of Pharmaceutics (AJP), 2017)
Aim: To study the effect of 5-R-thio-tetrazolo[1,5-Ñ]quinazoline derivatives on the physical performance in different types of physical exercise. Materials and Methods: The experiments were performed on Wistar white male rats weighing 190-210 g. The investigated substances and a comparator, 2-ethylthiobenzymidazol hydrobromide, were injected intraperitoneally to animals OD during 5 days in ED50 doses. Physical performance of rats was assessed by treadmill running tests at a speed of 42 m/min with a 10Â° slope angle and holding rats at a 15 rpm rotarod test. The study was performed on the day 5 of the experiment, 40 min after the past injection. Results and Discussion: We revealed that a 5-day course administration of 5-R-thio-tetrazolo[1,5-c]quinazoline derivatives at an ED50 dose contributed to growing the length of a rat treadmill running. The results of the test presented that physical endurance of animals grew with compounds KB-10, KB-28, KB-51, and KB-55 by 47.1, 60.7, 32.3, and 46.0 %, respectively. The duration of holding rats on rotarods with a pharmacological correction was 41.2-71.4 % higher than in the control group. The dynamics of physical endurance against treadmill running and rotarod tests results in the group of animals administered the reference medicine, 2-ethylthiobenzymidazol hydrobromide, made up 50.7 and 59.4% compared to the control, respectively. Conclusion: KB-28 (sodium 2-(tetrazolo[1,5-c]quinazoline-5-iltio)acetate) demonstrated the greatest effect on physical endurance of study participants among all 5-R-thio-tetrazolo[1,5-c]quinazoline derivatives. This substance was not only similar with the reference medicine in efficacy but also had ED50 19 times lower than reference actoprotector.